A Cu-Y with excellent performance 2 O 3 -CNTs-TiO 2 Preparation method of composite material

Through electrostatic adsorption technology and mechanical alloying method, carbon nanotubes and Ti are uniformly distributed in the copper matrix to generate TiC to improve the binding strength, and Y2O3 and CNTs are introduced to enhance the material performance, solving the problem of insufficient strength of copper alloys and achieving excellent conductivity and mechanical properties.

CN116179881BActive Publication Date: 2025-04-11HEFEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211685221.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-27
Publication Date
2025-04-11
Estimated Expiration
2042-12-27

AI Technical Summary

Technical Problem

While maintaining conductive properties, increasing the strength of copper alloys is a problem, especially because the uneven dispersion of carbon nanotubes in the copper matrix causes the bonding strength to be low on the interface with the copper matrix.

Method used

Electrostatic adsorption technology is used to adsorb carbon nanotubes on the copper matrix, and Ti is introduced during mechanical alloying. TiC is generated by reacting Ti with carbon nanotubes to improve the bonding strength of carbon nanotubes and copper, and uniformly dispersed Y2O3 and CNTs are introduced to jointly enhance the strength and conductivity of the material.

Benefits of technology

The uniform distribution of carbon nanotubes in the copper matrix is ​​achieved, the strength and conductivity of the material are improved, and excellent performance is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116179881B_ABST
    Figure CN116179881B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of copper-based composite materials and discloses a Cu-Y 2 O 3 ‑CNTs‑TiO 2 The preparation method of the composite material comprises the following steps: Step 1, preparing Cu-Y alloy powder by gas atomization technology, placing the Cu-Y alloy ingot in a vacuum melting furnace, pouring the molten metal liquid from the melting furnace into a 1300°C tundish crucible at a constant temperature of 1400°C under vacuum conditions, introducing it into a high-pressure gas atomizer after insulation for 7-9 minutes, and finally collecting it by a cyclone separator to screen out Cu-Y alloy powder with an average particle size of 15-50 um. The present invention adsorbs carbon nanotubes on a copper matrix by electrostatic adsorption technology, which can ensure the uniform distribution of carbon nanotubes in the sintered material; introduces metal powder Ti, which can react with carbon nanotubes to generate TiC during ball milling, thereby increasing the interface bonding strength between carbon nanotubes and copper matrix; by introducing uniformly dispersed Y 2 O 3 Together with CNTs, the strength and conductivity of copper alloys are synergistically enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper-based composite materials, and in particular to a method for preparing a Cu-Y2O3-CNTs-TiO2 composite material with excellent performance. Background Art

[0002] With the rapid development of science and technology, modern electronic devices have an increasingly high demand for electrical conductivity, and power loss associated with resistance has aroused great interest. Pure copper has good electrical conductivity, high thermal conductivity, and good processing performance, and is widely used in electronic packaging, power transmission and other fields. However, the mechanical properties of copper are too low, which limits its application. Therefore, while maintaining its electrical conductivity, improving the strength of copper alloys has become an important task in the development of high-conductivity copper alloys.

[0003] Dispersion-strengthened copper alloys were developed by introducing uniform and fine dispersed particles into the copper matrix. Dispersed particles can effectively hinder the movement of dislocations, thereby greatly improving the strength of copper alloys. Compared with precipitation-strengthened copper alloys, the conductivity will not be reduced much. The Cu-Y2O3 alloy developed by powder metallurgy technology can increase its strength to 300MPa, and its conductivity can reach 90%IACS. Carbon nanotubes (CNTs) are a one-dimensional quantum material with a special structure with a radial size of nanometers and an axial size of micrometers. Due to its excellent mechanical and electrical properties, it has attracted widespread attention and is considered to be an ideal fiber reinforcement phase for preparing composite materials. Studies have shown that adding a small amount of carbon nanotubes to copper-based materials can greatly improve the strength and conductivity of the material. However, CNTs have low surface activity and poor wettability, resulting in low interfacial bonding strength with most metal matrices. At the same time, due to the high surface energy, they tend to agglomerate in the copper matrix. The above shortcomings make it difficult for carbon nanotube-enhanced copper-based materials to achieve theoretical performance.

[0004] In order to solve the problem of dispersion of carbon nanotubes in copper matrix, many new technologies have been developed. Electrostatic adsorption technology is a one-step adsorption method that does not introduce other impurities. This novel method is based on the potential difference between copper and carbon nanotubes. Carboxylated carbon nanotubes are hydrophilic and have a negative potential in hydrochloric acid solution. However, under the same conditions, the electronegativity of copper powder is weaker than that of chlorine atoms, so it has a positive potential. Therefore, by adjusting and controlling the pH value of the solution after the two powders are immersed, the copper powder and carbon nanotubes can be attracted together.

[0005] The present invention combines electrostatic adsorption and mechanical alloying technology. The carbon nanotubes are evenly distributed in the copper matrix through the electrostatic adsorption technology. Ti is added during the mechanical alloying process. Ti can react with the carbon nanotubes to generate TiC, thereby improving the bonding strength between the carbon nanotubes and copper, and finally obtaining a Cu-Y2O3-CNTs-TiO2 composite material with excellent performance. Summary of the invention

[0006] In order to solve the technical problems raised in the background technology, the present invention provides a method for preparing a Cu-Y2O3-CNTs-TiO2 composite material with excellent performance.

[0007] The present invention is implemented by the following technical scheme: A method for preparing a Cu-Y2O3-CNTs-TiO2 composite material with excellent performance comprises the following steps:

[0008] Step 1: Prepare Cu-Y alloy powder by gas atomization technology, place the Cu-Y alloy ingot in a vacuum melting furnace, pour the molten metal from the melting furnace into a 1300°C tundish crucible at a constant temperature of 1400°C under vacuum conditions, and introduce it into a high-pressure gas atomizer after being kept warm for 7-9 minutes, and finally collect it by a cyclone separator to screen out Cu-Y alloy powder with an average particle size of 15-50 um;

[0009] Step 2: Ultrasonic dispersion of carbon nanotubes in deionized water for 15-20 min. At the same time, electrolytic copper powder with a particle size of 1-3 μm was ball-milled into flakes and mixed in deionized water. The two solutions were then mixed and placed in a magnetic stirrer. Hydrochloric acid solution was added to adjust the pH value of the Cu powder suspension to 4.0. The solution was stirred until it was completely evaporated, and the beaker was placed in a drying oven at 120-140°C for 12 hours to finally obtain carbon nanotube / Cu2O composite powder.

[0010] Step 3: Place the Cu-Y alloy powder prepared by gas atomization, the carbon nanotube / Cu2O composite powder obtained by electrostatic adsorption, and the Ti powder in a ball mill, assemble them in an argon atmosphere in a glove box, with a ball-to-powder ratio of 8:5, and then ball mill them on a planetary ball mill at a speed of 300-500rpm for 12-64h;

[0011] Step 4: After the ball-milled powder is fully ground in a mortar, it is placed in a ceramic sintering boat, placed in a tubular furnace at a high temperature of 600°C for 2 hours under a hydrogen atmosphere, and reduced to obtain a Cu-Y2O3-CNTs-TiO2 alloy powder;

[0012] Step 5. Weigh 12-13g of the composite powder obtained in step 4, grind it and put it into a graphite mold. Pre-press it at a pressure of 3MPa. After the mold is placed in the sintering furnace chamber, evacuate the pressure in the furnace chamber to -10MPa and maintain the vacuum state. Set the sintering program to sinter the sample under current and pressure.

[0013] As a further improvement of the above solution, in step 1, the atomization pressure is 5 MPa, and the diameter of the guide tube is set to 3 mm to control the particle size.

[0014] As a further improvement of the above scheme, in step 2, the temperature of the magnetic stirrer is 120-130° C., and the stirring speed is 160 rpm.

[0015] As a further improvement of the above solution, in step three, the particle size of the Ti powder is 3-5 um, and the glove box model is ZKX.

[0016] As a further improvement of the above solution, in step 4, the model of the tube furnace is GSL-1700X.

[0017] As a further improvement of the above scheme, in step 5, the sintering program is set as follows: adjusting the initial pressure to 10 MPa, heating from the initial temperature to 900°C at a rate of 100°C / min, during which the pressure is uniformly increased from 10 MPa to 50 MPa, and then rapidly cooled after keeping warm for 5 minutes.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention firstly adsorbs carbon nanotubes on a copper matrix by electrostatic adsorption technology, thereby ensuring uniform distribution of carbon nanotubes in the sintered material; introduces metal powder Ti, which can react with carbon nanotubes to generate TiC during ball milling, thereby increasing the interface bonding strength between the carbon nanotubes and the copper matrix; and introduces uniformly dispersed Y2O3 and CNTs, thereby synergistically enhancing the strength and conductivity of the copper alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM morphology of the carbon nanotubes used in the present invention.

[0021] Figure 2 This is the tensile fracture morphology of the Cu-Y2O3-CNTs-TiO2 material in the invention.

[0022] Figure 3 This is a preparation flow chart of the invented Cu-Y2O3-CNTs-TiO2 material. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0024] The specific examples of the present invention explore the effect of ball milling time on the properties of the prepared materials. The ball milling times in specific examples 1-3 are 12 h, 32 h, and 64 h, respectively.

[0025] Example 1

[0026] Step 1: Prepare Cu-Y alloy powder by gas atomization technology, place the Cu-Y alloy ingot in a vacuum melting furnace, pour the molten metal from the melting furnace into a 1300°C tundish crucible at 1400°C under vacuum conditions, and then introduce it into a high-pressure gas atomizer after being kept warm for 8 minutes. Finally, it is collected by a cyclone separator to screen out Cu-Y alloy powder with an average particle size of 15-50 um;

[0027] Step 2: Ultrasonic dispersion of carbon nanotubes in deionized water for 18 min. At the same time, electrolytic copper powder with a particle size of 1-3um was ball-milled into flakes and mixed in deionized water. The two solutions were then mixed and placed in a magnetic stirrer. Hydrochloric acid solution was added to adjust the pH value of the Cu powder suspension to 4.0. Stir until the solution is completely evaporated, and the beaker was placed in a drying oven at 130°C for 12 hours to finally obtain carbon nanotube / Cu2O composite powder.

[0028] Step 3: Place the Cu-Y alloy powder prepared by atomization, the carbon nanotube / Cu2O composite powder obtained by electrostatic adsorption, and the Ti powder in a ball mill, assemble them under an argon atmosphere in a glove box, with a ball-to-powder ratio of 8:5, and then ball mill them on a planetary ball mill at a speed of 400 rpm for 12 h.

[0029] Step 4: After the ball-milled powder is fully ground in a mortar, it is placed in a ceramic sintering boat, placed in a tubular furnace high-temperature furnace and kept at 600°C for 2 hours under a hydrogen atmosphere to reduce and obtain Cu-Y2O3-CNTs-Ti alloy powder.

[0030] Step 5: Weigh 12-13g of the composite powder obtained in step 4, grind it and put it into a graphite mold, pre-press it at a pressure of 3MPa, put the mold into the sintering furnace, evacuate the pressure in the furnace to -10MPa, and maintain the vacuum state, set the sintering program, and sinter the sample under current and pressure. The sintering program is set as follows: adjust the initial pressure to 10MPa, increase the temperature from the initial temperature to 900℃ at a rate of 100℃ / min, at this stage, the pressure is evenly increased from 10MPa to 50MPa, keep warm for 5min and then cool rapidly.

[0031] Example 2

[0032] Step 1: Prepare Cu-Y alloy powder by gas atomization technology, place the Cu-Y alloy ingot in a vacuum melting furnace, pour the molten metal from the melting furnace into a 1300°C tundish crucible at 1400°C under vacuum conditions, and then introduce it into a high-pressure gas atomizer after being kept warm for 8 minutes. Finally, it is collected by a cyclone separator to screen out Cu-Y alloy powder with an average particle size of 15-50 um;

[0033] Step 2: Ultrasonic dispersion of carbon nanotubes in deionized water for 18 min. At the same time, electrolytic copper powder with a particle size of 1-3um was ball-milled into flakes and mixed in deionized water. The two solutions were then mixed and placed in a magnetic stirrer. Hydrochloric acid solution was added to adjust the pH value of the Cu powder suspension to 4.0. Stir until the solution is completely evaporated, and the beaker was placed in a drying oven at 130°C for 12 hours to finally obtain carbon nanotube / Cu2O composite powder.

[0034] Step 3: Place the Cu-Y alloy powder prepared by gas atomization, the carbon nanotube / Cu2O composite powder obtained by electrostatic adsorption, and the Ti powder in a ball mill. The assembly was performed under an argon atmosphere in a glove box with a ball-to-powder ratio of 8:5, and then ball milled on a planetary ball mill at a speed of 400 rpm for 32 h.

[0035] Step 4: After the ball-milled powder is fully ground in a mortar, it is placed in a ceramic sintering boat, placed in a tubular furnace high-temperature furnace and kept at 600°C for 2 hours under a hydrogen atmosphere to reduce and obtain Cu-Y2O3-CNTs-Ti alloy powder.

[0036] Step 5: Weigh 12-13g of the composite powder obtained in step 4, grind it and put it into a graphite mold, pre-press it at a pressure of 3MPa, put the mold into the sintering furnace, evacuate the pressure in the furnace to -10MPa, and maintain the vacuum state, set the sintering program, and sinter the sample under current and pressure. The sintering program is set as follows: adjust the initial pressure to 10MPa, increase the temperature from the initial temperature to 900℃ at a rate of 100℃ / min, at this stage, the pressure is evenly increased from 10MPa to 50MPa, keep warm for 5min and then cool rapidly.

[0037] Example 3

[0038] Step 1: Prepare Cu-Y alloy powder by gas atomization technology, place the Cu-Y alloy ingot in a vacuum melting furnace, pour the molten metal from the melting furnace into a 1300°C tundish crucible at 1400°C under vacuum conditions, and then introduce it into a high-pressure gas atomizer after being kept warm for 8 minutes. Finally, it is collected by a cyclone separator to screen out Cu-Y alloy powder with an average particle size of 15-50 um;

[0039] Step 2: Ultrasonic dispersion of carbon nanotubes in deionized water for 18 min. At the same time, electrolytic copper powder with a particle size of 1-3um was ball-milled into flakes and mixed in deionized water. The two solutions were then mixed and placed in a magnetic stirrer. Hydrochloric acid solution was added to adjust the pH value of the Cu powder suspension to 4.0. Stir until the solution is completely evaporated, and the beaker was placed in a drying oven at 130°C for 12 hours to finally obtain carbon nanotube / Cu2O composite powder.

[0040] Step 3: Place the Cu-Y alloy powder prepared by gas atomization, the carbon nanotube / Cu2O composite powder obtained by electrostatic adsorption, and the Ti powder in a ball mill. The assembly was performed under an argon atmosphere in a glove box with a ball-to-powder ratio of 8:5, and then ball milled on a planetary ball mill at a speed of 400 rpm for 64 h.

[0041] Step 4: After the ball-milled powder is fully ground in a mortar, it is placed in a ceramic sintering boat, placed in a tubular furnace high-temperature furnace and kept at 600°C for 2 hours under a hydrogen atmosphere to reduce and obtain Cu-Y2O3-CNTs-Ti alloy powder.

[0042] Step 5: Weigh 12-13g of the composite powder obtained in step 4, grind it and put it into a graphite mold, pre-press it at a pressure of 3MPa, put the mold into the sintering furnace, evacuate the pressure in the furnace to -10MPa, and maintain the vacuum state, set the sintering program, and sinter the sample under current and pressure. The sintering program is set as follows: adjust the initial pressure to 10MPa, increase the temperature from the initial temperature to 900℃ at a rate of 100℃ / min, at this stage, the pressure is evenly increased from 10MPa to 50MPa, keep warm for 5min and then cool rapidly.

[0043] The following table compares the hardness, tensile strength and conductivity of the Cu-Y2O3-CNTs-TiO2 blocks prepared at different ball milling times in Examples 1-3.

[0044]

[0045] As can be seen from the table, the performance of the material first improves with the increase of ball milling time. At this stage, as the ball milling progresses, the distribution of the second phase in the material becomes more uniform, and the grains are refined, which improves the performance. However, as the ball milling time is further extended, the cold welding effect occupies a dominant position, and the structure of the carbon nanotubes may be destroyed, which reduces the performance.

[0046] At the same time, from Figure 1 It can be seen that carbon nanotubes that have not been ultrasonically dispersed are very easy to agglomerate, and a single carbon nanotube is in the shape of a long tube with a size at the nanometer level. Figure 2 It is reflected that there are many evenly dispersed dimples on the fracture surface, and the material exhibits ductile fracture.

[0047] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for preparing a Cu-Y2O3-CNTs-TiO2 composite material with excellent performance, characterized in that: The steps include: Step 1: Prepare Cu-Y alloy powder by gas atomization technology, place the Cu-Y alloy ingot in a vacuum melting furnace, pour the molten metal from the melting furnace into a 1300°C tundish crucible at a constant temperature of 1400°C under vacuum conditions, and introduce it into a high-pressure gas atomizer after being kept warm for 7-9 minutes, and finally collect it by a cyclone separator to screen out Cu-Y alloy powder with an average particle size of 15-50 um; Step 2: Ultrasonic dispersion of carbon nanotubes in deionized water for 15-20 min. At the same time, electrolytic copper powder with a particle size of 1-3 um is ball-milled into flakes and mixed in deionized water. The two solutions are then mixed and placed in a magnetic stirrer. Hydrochloric acid solution is added to adjust the pH value of the Cu powder suspension to 4.

0. The solution is stirred until it is completely evaporated, and the beaker is placed in a drying oven at 120-140°C for 12 hours to obtain carbon nanotube / Cu2O composite powder by the above-mentioned electrostatic adsorption. Step 3: Place the Cu-Y alloy powder prepared by atomization, the carbon nanotube-Cu2O composite powder obtained by electrostatic adsorption, and the Ti powder in a ball mill, assemble them in an argon atmosphere in a glove box, with a ball-to-powder ratio of 8:5, and then ball mill them on a planetary ball mill at a speed of 300-500rpm for 12-64h; Step 4: After the ball-milled powder is fully ground in a mortar, it is placed in a ceramic sintering boat, placed in a tubular furnace at a high temperature of 600°C for 2 hours under a hydrogen atmosphere, and reduced to obtain a Cu-Y2O3-CNTs-TiO2 alloy powder; Step 5. Weigh 12-13g of the composite powder obtained in step 4, grind it and put it into a graphite mold. Pre-press it at a pressure of 3MPa. After the mold is placed in the sintering furnace chamber, evacuate the pressure in the furnace chamber to -10MPa and maintain the vacuum state. Set the sintering program to sinter the sample under current and pressure.

2. The method for preparing a Cu-Y2O3-CNTs-TiO2 composite material with excellent performance as claimed in claim 1, characterized in that: In the step 1, the atomization pressure is 5 MPa, and the diameter of the flow guide tube is set to 3 mm to control the particle size.

3. The method for preparing a Cu-Y2O3-CNTs-TiO2 composite material with excellent performance as claimed in claim 1, characterized in that: In the step 2, the temperature of the magnetic stirrer is 120-130° C., and the stirring speed is 160 rpm.

4. The method for preparing a Cu-Y2O3-CNTs-TiO2 composite material with excellent performance as claimed in claim 1, characterized in that: In the step 3, the particle size of the Ti powder is 3-5 um, and the glove box model is ZKX.

5. The method for preparing a Cu-Y2O3-CNTs-TiO2 composite material with excellent performance as claimed in claim 1, characterized in that: In step 4, the model of the tube furnace is GSL-1700X.

6. The method for preparing a Cu-Y2O3-CNTs-TiO2 composite material with excellent performance as claimed in claim 1, characterized in that: In step five, the sintering program is set as follows: adjusting the initial pressure to 10 MPa, heating from the initial temperature to 900° C. at a rate of 100° C. / min, during which the pressure is uniformly increased from 10 MPa to 50 MPa, and then rapidly cooled after keeping the temperature for 5 minutes.

Citation Information

Patent Citations

  • Method of CNTs / TiO2 nano composite powder enhanced Cu-based composite material

    CN107299237A

  • Preparation method of in-situ self-generated Cu2O particle-induced quasi-continuous net structure CNTs / Cu-based composite material

    CN110343891A